Development of 2-aminooxazoline 3-azaxanthene β-amyloid cleaving enzyme (BACE) inhibitors with improved selectivity against Cathepsin D12. Issue 6 (8th May 2017) - Low, Jonathan D.; Bartberger, Michael D.; Chen, Kui; Cheng, Yuan; Fielden, Mark R.; Gore, Vijay; Hickman, Dean; Liu, Qingyian; Allen Sickmier, E.; Vargas, Hugo M.; Werner, Jonathan; White, Ryan D.; et al.
Abstract : We report the discovery of an orally efficacious 3-aza-aminooxazoline-BACE1 inhibitor with 1 800 000× fold selectivity against CatD and no retinal effects in an early screening rat toxicology study. Abstract : As part of an ongoing effort at Amgen to develop a disease-modifying therapy for Alzheimer's disease, we have previously used the aminooxazoline xanthene (AOX) scaffold to generate potent and orally efficacious BACE1 inhibitors. While AOX-BACE1 inhibitors demonstrated acceptable cardiovascular safety margins, a retinal pathological finding in rat toxicological studies demanded further investigation. It has been widely postulated that such retinal toxicity might be related to off-target inhibition of Cathepsin D (CatD), a closely related aspartyl protease. We report the development of AOX-BACE1 inhibitors with improved selectivity against CatD by following a structure- and property-based approach. Our efforts culminated in the discovery of a picolinamide-substituted 3-aza-AOX-BACE1 inhibitor absent of retinal effects in an early screening rat toxicology study.